An Overview of the Japanese Distribution System : The Case of the Automobile Industry - Shirai, Sayuri (IMF Working Papers; Working Paper ;, 1994)
This paper surveys the recent literature on the Japanese distribution system to consider two propositions: first, that the system is inefficient, and second that prices of imported products tend to be higher in Japan than in other markets. Most of the literature demonstrates that the system is efficient. However, the efficiency has not necessarily resulted in high social welfare as consumers have had limited access to various product lines or paid high prices for some products. This paper examines the distribution system in the automobile industry to promote understanding about the impacts of the system on price differentials.